ANALISIS PENGARUH KREATIVITAS PRODUK DAN PERSEPSI KONSUMEN TERHADAP PERTUMBUHAN PENJUALAN PADA UMKM BATIK DI KABUPATEN PURBALINGGA - Handayani, Juli (DFAME Digital Financial Accounting Management Economics Journal, 2024)
Product creativity and consumer perception are two very relevant aspects to analyze, because both have a significant impact on sales growth. Product creativity creates uniqueness and appeal for consumers, while consumer perception plays an important role in forming a positive image of the product. The aim of this research is to examine the relationship between product creativity and the sales growth of Batik MSMEs in Purbalingga Regency and to examine the relationship between consumer perceptions and the sales growth of Batik MSMEs in Purbalingga Regency. Using multiple regression analysis, 97 respondents were tested using a questionnaire instrument. The results of this research are that product creativity has a positive effect on the sales growth of Batik MSMEs in Purbalingga Regency and consumer perception has a positive effect on the sales growth of Batik MSMEs in Purbalingga Regency.